PENGARUH RENTANG WAKTU PENINGKATAN SALINITAS TERHADAP KELULUSHIDUPAN DAN PERTUMBUHAN LARVA IKAN BAUNG (H. nemurus) - Ahlun Nazar; Fakhrunnas MA Jabbar; Hisra Melati (UIR Press, 2019)
This research is expected to be useful especially for fish farmers as additional information in raising baung fish. The method used was an experimental method using a Completely Randomized Design (CRD) with 4 treatments and 3 replications namely: P1 = 5 ‰ per 3 days 7 ‰ per 3 days, 9 ‰ per 3 days, P2 = 5 ‰ per 5 days 7 ‰ per 5 days 9 ‰ per 5 days, P3 = 5 ‰ per 7 days 7 ‰ per 7 days 9 ‰ per 7 days, P4 = 5 ‰ per 9 days 7 ‰ per 9 days 9 ‰ per 9 days. The baung fish used for the study was obtained from spawning at the Fish Seed Center (BBI) of the Faculty of Agriculture, Riau Islamic University with a weight of 0.14 gr of baung fish/tail and 1.6 cm in length/tail. The container used is a jar a size of 10 liters. From the results of the study obtained the best absolute weight growth and absolute length of the treatment (P4) with a weight of 4.35 gr and a length of 1.84 cm, followed by treatment (P2) with a weight of 3.96 gr and P3 a length of 1.82 cm, (P3 ) weighing 3, 75 gr and P2, 1.73 cm long, and the lowest in treatment (P1) with a weight of 2.64 grams and a length of 1.28 cm. The daily weight growth rate in the treatment group (P2) was 17.31%, (P2) 15.17%, (P4) 13.18%, and the lowest (P3) was 12.60%. The best survival rate for treatment (P4) was 72.00%, followed by treatment (P3) at 54.67%, and the lowest for treatment (P1) was 6, 67%. The results of water quality measurements in this study were temperature 28-300C, pH 6-7, dissolved oxygen 0.4 ppm, ammonia 0.05 ppm. Based on the observations of water quality during the study was within the range of tolerance for the growth and life of baung fish.